Achievements in the mass media in Uzbekistan during the covid19 pandemy - Джумаева, Shakhnoza (Результаты научных исследований в условиях пандемии (COVID-19), 2022)
The article highlights the activities of the mass media in the Republic of Uzbekistan during the COVID-19 pandemic, including thecoverage of preventive measures during the pandemic, as well as the role of the media in the implementation of online education in the school education system. At the same time, the achievements in the field of media coverage of preventive work against COVID-19 in the country were described